PELATIHAN PENGENDALIAN PENYAKIT LAYU PADA TANAMAN JAHE DI DESA TARO KABUPATEN GIANYAR - I N. Wijaya; W. Adiartayasa; M. Sritamin; I G. Ngurah Bagus (Buletin Udayana Mengabdi, 2013)
Training on ginger wilt diseases was held at Taro village, Gianyar regency on 18 st July 2013. The activitiesaimed how to know control of ginger wilt diseases. The training was attended by 25 participants from local farmergroups of Taro village. The methods used in activities were lectures, demonstration and practice in the gingerfield. All participants participated enthusiastically and hope they have the next intensive training again.